1998
DOI: 10.1038/sj.bjp.0701795
|View full text |Cite
|
Sign up to set email alerts
|

Differential mechanism for the cell surface sorting and agonist‐promoted internalization of the α1B‐adrenoceptor

Abstract: 1 a 1B -adrenoceptors are localized at a steady state in the plasma membrane in untreated cells, and internalize to intracellular vesicles when exposed to agonist. Flow cytometry analysis with an anti-Nterminus-antibody (1B-N1-C, ) facilitated the quanti®cation of cell surface a 1B -adrenoceptor. Also, the cellular distribution of a 1B -adrenoceptors was visually monitored by immunocytochemical confocal microscopy. 2 Utilizing this combined approach, we have examined the molecular mechanism for cellular tracki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 33 publications
0
22
1
Order By: Relevance
“…This is in agreement with the results of a previous study showing that actin depolymerization caused missorting of the ␤2-AR to lysosomes instead of recycling vesicles (10). In contrast with our findings, a previous study reported that cytochalasin D could inhibit the internalization of the ␣1b-AR in Chinese hamster ovary cells (26). However, several differences exist between the two studies, including the fact that in Chinese hamster ovary cells the internalization of the ␣1b-AR seemed to be clathrin-independent, whereas we have recently reported that in HEK-293 cells it involves clathrin-coated pits (6).…”
Section: Discussioncontrasting
confidence: 57%
“…This is in agreement with the results of a previous study showing that actin depolymerization caused missorting of the ␤2-AR to lysosomes instead of recycling vesicles (10). In contrast with our findings, a previous study reported that cytochalasin D could inhibit the internalization of the ␣1b-AR in Chinese hamster ovary cells (26). However, several differences exist between the two studies, including the fact that in Chinese hamster ovary cells the internalization of the ␣1b-AR seemed to be clathrin-independent, whereas we have recently reported that in HEK-293 cells it involves clathrin-coated pits (6).…”
Section: Discussioncontrasting
confidence: 57%
“…Further studies are required to elucidate whether such regulation is a more generalized mechanism that participates in the trafficking of other chemoattractant receptors. As for the regulation of other members of the GPCR superfamily, the conflicting observations regarding the regulation of muscarinic cholinergic receptor and adrenergic receptor trafficking by cytoskeleton components, combined with our present study, suggest that different receptors that belong to the superfamily of GPCR are divergently regulated in this respect (54,59,60). However, it is interesting to note that in similarity to the role of actin filaments in the regulation of CXCR1 and CXCR2 recycling, the recycling process of ␤ 2 -adrenergic receptors was also dependent on actin filaments (54).…”
Section: Discussionmentioning
confidence: 78%
“…For example, both latrunculin A and cytochalasin D disrupt actin cytoskeleton, but marked attenuation in internalization of endothelin or epidermal growth factor receptors is seen only with latrunculin A and not with cytochalasin D (8). In contrast, cytochalasin D blocks agonist-induced internalization of ␣ 1B -adrenergic receptor (9), underscoring the complexity of actin dynamics. Considering these contrasting results with chemical agents, we sought to investigate the role of cortical actin cytoskeleton in agonist-mediated ␤ 2 AR internalization by using a chemical agent that disrupts the actin cytoskeleton and mutants of the actin-binding protein cofilin known to alter the integrity of the actin cytoskeleton.…”
mentioning
confidence: 98%